THE DISTINCTIVE FEATURES OF THE ENGLISH BUSINESS CORRESPONDENCE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
With the development of economic globalization, international business has grown considerably in the past two decades. As one of the main means of communication in the international business world, English business correspondence writing plays an indispensable role during the business procedure. The business correspondence initiates and maintains the business relationship between the trade members, and its quality concerns the success or failure of a business deal to a large extent. A well-written business letter will not only accelerate the ongoing deal, but also create a trustful relationship between the partners, which will bring potential benefits in future contacts. On the contrary, if a business letter is inappropriately drafted, it will cause misunderstandings during the transaction, and this may bring successive troubles in the following steps or even result in a total failure of the deal.